Linking Social Capital, Knowledge Sharing, and Individual Outcomes: Future Research Agenda - Helmy, Irfan; Parmin, Parmin; Fitri, Aprilia Wahyuning; Supriyani, Tari; Amalia, Dike (AIBPM Publisher, 2023)
In today's knowledge-based economy, knowledge sharing is essential for organizations to be successful. However, knowledge sharing can be challenging due to a lack of trust, fear of losing power or status, cultural barriers, and lack of incentives. This study aims to create a conceptual model to understand better the relationship between social capital and the knowledge sharing process. We use a literature review approach to understand what comes before and after knowledge sharing. By looking at existing research, we want to find out the things that lead to knowledge sharing and the results of it. This helps us get a full picture of how sharing knowledge works and what factors play a role The study will examine how social capital dimensions (structural capital, relational capital, and cognitive capital) affect knowledge collecting and knowledge. The findings of this study will help practitioners and managers to create an environment that encourages people to share their knowledge, leading to increased innovation, productivity, and decision-making effectiveness.